Successful hysteroscopic management of two cases of interstitial pregnancy - Jokanović, Predrag; Rakić, Aleksandar (Vojnosanitetski pregled, 2023)
Introduction. Interstitial pregnancy (IP) is the rarest type of tubal pregnancy with a high rupture rate and often re-mains asymptomatic in the first 10–12 gestational weeks. Therefore, the timing of the diagnosis is crucial for success-ful management. Case report. Two patients, aged 28 and 22, were diagnosed with IP using transvaginal ultrasound. Both patients were asymptomatic, with initial serum βhCG of 6,664 mIU/mL and 4,641 mIU/mL, respectively. Since they refused treatment with methotrexate and wanted to preserve their fertility, we performed operative hysteroscopy with resection and evacuation of the gestational tissue. The procedures were uneventful. The βhCG levels dropped sig-nificantly, and the patients were discharged after three and four hospital days, respectively. Conclusion. Using hyster-oscopic procedures, we successfully treated two asympto-matic patients with IP of gestational age < 10 weeks by ul-trasonography and levels of serum βhCG < 7,000 mIU/mL. With the occurrence of IP but also the numerous advantages of hysteroscopy, large, multicenter studies are necessary to further investigate the place of this approach as a single treatment method for IP. Trends and consequences observed during the COVID-19 pandemic correlate with the importance of timely diagnosis of ectopic pregnancies, the benefits of a minimally invasive approach in their treat-ment, and epidemiologically justified shorter hospital stays.
Keywords: gynecologic surgical procedures; minimally invasive surgical procedures; pregnancy, ectopic